Moral Injury, Australian Veterans and the Role of Chaplains: An Exploratory Qualitative Study - Hodgson, Timothy J. (Journal of religion and health, 2021)
Military personnel deployed to war zones or assigned to other morally challenging military duties are likely to be exposed to potentially morally injurious events (PMIE) that may inflict a moral injury (MI). This qualitative study formed ‘Phase 1’ of a larger study into PMIEs experienced by Australian veterans and the potential pastoral/spiritual care role of chaplains. Two seminars were conducted that involved 10 veterans being interviewed and audio recorded about their deployment experiences to evaluate whether there was any evidence among Australian veterans of a PMIE. Narrative data analysis indicated that all participants had been exposed to, or were involved in, a PMIE of one kind or another. Seven key themes were identified from the analyzed qualitative data: (i) immoral acts, (ii) death and injury, (iii) betrayal, (iv) ethical dilemmas, (v) disproportionate violence, (vi) retribution and (vii) religious/spiritual issues. Given this preliminary PMIE evidence identified, there is a need for further research, as well as the development of a suitable moral injury assessment scale appropriate for Australian veterans. Furthermore, given the ethical, moral, and spiritual issues involved, the implementation of a rehabilitation program suitable for Australian veterans which can be provided by chaplains is also suggested—namely ‘Pastoral Narrative Disclosure.’ It is argued that moral injury needs to be recognized, not just as an issue affecting individual personnel and their families, but is also a community health, organizational and government responsibility.